Pathogenic and Low-Frequency Variants in Children With Central Precocious Puberty - Neocleous, Vassos; Fanis, Pavlos; Toumba, Meropi; Gorka, Barbara; Kousiappa, Ioanna; Tanteles, George A.; Iasonides, Michalis; Nicolaides, Nicolas C.; Christou, Yiolanda P.; Michailidou, Kyriaki; Nicolaou, Stella; Papacostas, Savvas S.; et al. (Frontiers in Endocrinology, 2021)
Background Central precocious puberty (CPP) due to premature activation of GnRH secretion results in early epiphyseal fusion and to a significant compromise in the achieved final adult height. Currently, few genetic determinants of children with CPP have been described. In this translational study, rare sequence variants in MKRN3, DLK1, KISS1, and KISS1R genes were investigated in patients with CPP. Methods Fifty-four index girls and two index boys with CPP were first tested by Sanger sequencing for the MKRN3 gene. All children found negative (n = 44) for the MKRN3 gene were further investigated by whole exome sequencing (WES). In the latter analysis, the status of variants in genes known to be related with pubertal timing was compared with an in-house Cypriot control cohort (n = 43). The identified rare variants were initially examined by in silico computational algorithms and confirmed by Sanger sequencing. Additionally, a genetic network for the MKRN3 gene, mimicking a holistic regulatory depiction of the crosstalk between MKRN3 and other genes was designed. Results Three previously described pathogenic MKRN3 variants located in the coding region of the gene were identified in 12 index girls with CPP. The most prevalent pathogenic MKRN3 variant p.Gly312Asp was exclusively found among the Cypriot CPP cohort, indicating a founder effect phenomenon. Seven other CPP girls harbored rare likely pathogenic upstream variants in the MKRN3. Among the 44 CPP patients submitted to WES, nine rare DLK1 variants were identified in 11 girls, two rare KISS1 variants in six girls, and two rare MAGEL2 variants in five girls. Interestingly, the frequent variant rs10407968 (p.Gly8Ter) of the KISS1R gene appeared to be less frequent in the cohort of patients with CPP. Conclusion The results of the present study confirm the importance of the MKRN3-imprinted gene in genetics of CPP and its key role in pubertal timing. Overall, the results of the present study have emphasized the importance of an approach that aligns genetics and clinical aspects, which is necessary for the management and treatment of CPP.